Health-related quality of life, mental and sleep disordes of patients with pulmonary arterial hypertension participating in the Polish PH treatment program - Kathie Sarzyńska; Beata Jankowska-Polańska (Journal of Education, Health and Sport)
Pulmonary arterial hypertension (PAH) is a rare, chronic disease, that leads to the development of a range of heart failure-related symptoms that directly affect an individual's functioning. The aim of the study was to assess health-related quality of life (HRQoL) of the PAH patients. Participants completed several specific survey questionnaires. The mean scores obtained in each domain of the PAH-SYMPACT HRQoL questionnaire were: cardiopulmonary symptoms 1.02±0.57, cardiovascular symptoms 0.54±0.5, physical effects 1.24±0.9, mental effects 0.99±SD=0.82. The average scores on the anxiety and depression scales were 5.33±3.31, 4.4±3.78, respectively, which indicates their low severity. The mean score obtained on the Pittsburgh Sleep Quality Scale (PSQI) was 8.7±4.64 and represented the to poor sleep quality affecting the study group. Sleep disorders were present in the majority of the subjects and had the most significant impact on reducing the HRQoL in the study group. Anxiety and depressive disorders were present in a small percentage of the subjects. The results showed that the best predictor of HRQoL evaluation is sleep quality assessment.